Sorafenib inhibits proliferation and invasion of human hepatocellular carcinoma cells via upregulation of p53 and suppressing FoxM1 - WEI Ji-chao; MENG Fan-di; QU Kai; WANG Zhi-xin; WU Qi-fei; ZHANG Ling-qiang; PANG Qing; LIU Chang (Acta Pharmacologica Sinica, 2017)
Aim: Forkhead box M1 (FoxM1) is a transcription factor that plays important roles in the pathogenesis and progression of human cancers, including hepatocellular carcinoma (HCC). The aim of this study was to examine the involvement of FoxM1 in the anti-cancer action of sorafenib, a multikinase inhibitor, in human HCC cells. Methods: HCC cell lines HepG2 and HuH-7 were tested. Cell viability was examined using MTT assay and cell invasion was determined with Transwell migration assay. The relevant mRNA expression was determined with RT-PCR, and the proteins were detected using Western blotting and immunofluorescence assays. RNA interference was used to modify the expression of p53 and FoxM1. HuH-7 cell line xenograft mice were used for in vivo study, which were treated with sorafenib (40 mg/kg, po) daily for 3 weeks. Results: Sorafenib (2–20 μmol/L) inhibited the proliferation of the cells in dose- and time-dependent manners with an IC50 value of nearly 6 μmol/L at 48 h. Sorafenib (6 μmol/L) markedly suppressed the cell invasion. Furthermore, sorafenib (2−6 μmol/L) dose-dependently decreased the expression of FoxM1, MMP-2, and Ki-67, and up-regulated that of p53 in the cells. Silencing p53 abolished the decrease of FoxM1 and increase of p53 in sorafenib-treated cells. Silencing FoxM1 significantly reduced the expression of MMP-2 and Ki-67, and enhanced the anti-proliferation action of sorafenib in the cells, whereas overexpression of FoxM1 increased the expression of MMP-2 and Ki-67, and abrogated the anti-proliferation action of sorafenib. In the xenograft mice, sorafenib administration decreased the tumor growth by 40%, and markedly increased the expression of p53, and decreased the expression of FoxM1, MMP-2, and Ki-67 in tumor tissues. Conclusion: Sorafenib inhibits HCC proliferation and invasion by inhibiting MMP-2 and Ki-67 expression due to up-regulation of P53 and suppressing FoxM1.